A conceptual model of customer relationship management alignment - Mohamed, Norshidah; Abdul Karim, Nor Shahriza; Mahmud, Murni; Ahlan, Abdul Rahman; Hussein, Ramlah; Kaur, Jasber (IADIS, 2012)
The paper proposes a conceptual model of customer relationship management (CRM) alignment. The research adopts the business-information system (IS) strategic alignment model, CRM process and technology perspectives and effectiveness of CRM as a basis. Based on a review of CRM, we propose CRM alignment to consist of business-IS strategic alignment and CRM process-IS alignment. The impact of CRM-alignment is CRM performance that is modeled using the Balanced Scorecard framework. As the research is in-progress, the results of pilot study are presented in the paper.